Development of retail and shopping centres in Ljubljana - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
Over the past 15 years Slovenia has gone through major economic and political changes. Retail was one of the economic activities that experienced the most proufound changes in the process of economic transition. In the paper the main characteristics of development of retail in Ljubljana with special regard to creation of new suburban shopping centres are presented. The main goal of the research was to analyse spatial distribution and functions of shopping centres and hypermarkets in Ljubljana. In order to establish whether shopping centres have started to develop social functions or are they still predominantly places of retail questionnaire survey in 5 largest shopping centres was conducted.
Keywords: geografija naselij; mesta; funkcije; trgovina na drobno; trgovski centri; nakupovalni centri; Ljubljana